NCM positive electrode particle coated with Ga-LLZO, LATP and CNT

By covering the large NCM particles of Ga-LLZO and LATP fine particles and covering the nano-carbon tubes, a channel for guiding lithium ions is formed, which solves the problem of insufficient positive electrode capacity and conductivity of solid-state batteries, and improves battery performance and service life , and reduces production costs.

CN222233673UActive Publication Date: 2024-12-24SUZHOU GUTAI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420358222.X
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-02-27
Publication Date
2024-12-24
Estimated Expiration
2034-02-27

AI Technical Summary

Technical Problem

The prior art is difficult to improve the capacitance and conductivity of the positive electrode in solid-state batteries, resulting in insufficient battery performance and the positive electrode material is easily eroded by electrolyte, affecting its service life.

Method used

NCM positive electrode particles coated with Ga-LLZO, LATP and CNT are used to coat large NCM particles through Ga-LLZO and LATP fine particles and coat nanocarbon tubes on the outside to form a channel for guiding lithium ions, improving conductivity and Protect large NCM particles and reduce the amount of cobalt used.

Benefits of technology

It significantly improves the conductivity of lithium ions and battery performance, extends the service life of the battery, and reduces the production cost and the use of cobalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222233673U_ABST
    Figure CN222233673U_ABST
Patent Text Reader

Abstract

The utility model relates to an NCM positive electrode particle coated with Ga-LLZO, LATP and CNT. The NCM positive electrode particle comprises a positive electrode substrate; the positive electrode slurry layer is coated on the positive electrode substrate, the positive electrode slurry layer comprises positive electrode slurry containing a binding agent and a plurality of positive electrode particles, and each positive electrode particle comprises an NCM large particle; the outer surface of the NCM large particle is coated by a plurality of Ga-LLZO fine particles and a plurality of LATP fine particles, so that the composite NCM large particle is integrally formed; wherein the Ga-LLZO fine particles and the LATP fine particles are distributed on the NCM large particles in a convex arc shape; a Ga-LLZO dielectric phase layer is formed between the bottoms of the Ga-LLZO fine particles and the NCM large particles, and an LATP dielectric phase layer is formed between the bottoms of the LATP fine particles and the NCM large particles. The CNT coated on the periphery of the composite NCM large particle is short-chain CNT, and the length of the short-chain CNT is between 0.5 micrometer and 1 micrometer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of positive electrode materials, in particular to NCM positive electrode particles coated with Ga-LLZO, LATP and CNT. Background Art

[0002] The battery is mainly formed by placing the positive electrode and the negative electrode in the electrolyte. The positive electrode is a large number of positive electrode conductive units (positive electrode materials, such as lithium cobalt oxide) mixed and dispersed in the slurry. Generally speaking, the positive electrode conductive unit must be mixed with the conductive slurry before it can be used on the electrode sheet and assembled into a battery. Therefore, the numerous positive electrode conductive units (positive electrode materials) are connected to each other through the conductive slurry. Therefore, the conductive slurry must have conductive properties or conductivity, so that free electrons can migrate in different positive electrode conductive units without consuming too much energy due to internal resistance, and achieve effective conduction. Therefore, when manufacturing the slurry, it is necessary to consider the use of specific conductive materials to adjust the conductivity of the slurry.

[0003] Generally, in order to increase conductivity, a plurality of positive electrode particles are filled in the positive electrode slurry, wherein the material of the positive electrode particles can be selected from NCM (lithium nickel cobalt manganese oxide), LMFP (lithium manganese iron phosphate), etc. or a mixture thereof, and the positive electrode particles are distributed in the positive electrode slurry.

[0004] In other patents of the applicant, in order to further increase the conductivity of the entire slurry, carbon nanotubes are added to the slurry to surround the positive electrode particles in the positive electrode material of the battery, and then the carbon nanotubes are used to bridge different positive electrode conductive units, thereby reducing the internal resistance generated by electrons crossing the slurry to another positive electrode conductive unit, thereby improving the conductivity of the entire positive electrode.

[0005] The above-mentioned prior art mainly increases the overall conductivity of the contents in the positive electrode slurry, thereby increasing the capacitance and conductivity of the entire positive electrode.

[0006] Based on the applicant's long experience in battery materials, the applicant hopes to propose a new design that can make the positive electrode of the current solid-state battery have higher capacity and conductivity, so as to further improve the performance of the battery. Utility Model Content

[0007] Therefore, the purpose of the present invention is to solve the above-mentioned problems in the prior art. The present invention proposes a NCM positive electrode particle coated with Ga-LLZO, LATP and CNT, forming a large NCM particle whose outer surface is coated with a large number of Ga-LLZO fine particles and LATP fine particles. Because the ability of the LATP fine particles to accommodate and evenly flow lithium ions is much higher than that of the large NCM particles, and the large NCM particles can be prevented from being corroded by the electrolyte, while extending the service life of the battery. In addition, a plurality of Ga-LLZO fine particles are attached to the surface of the plurality of large NCM particles, and the Ga-LLZO fine particles also have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the channels of lithium ions can be dispersed through the guidance of the dispersed Ga-LLZO fine particles and the LATP fine particles, so the design of the positive electrode of the present invention can make lithium ions have better channels. The present invention also coats nano carbon tubes, i.e. CNTs, on the outside of the large NCM particles coated with Ga-LLZO and LATP fine particles. The role of the carbon nanotubes is to form conductive bridges around various Ga-LLZO fine particles and LATP fine particles, so that electrons can be conducted on the composite NCM large particles. The framework of the utility model can provide stability for the overall positive electrode slurry structure, so the use of cobalt can be reduced.

[0008] In order to achieve the above-mentioned purpose, the utility model proposes a NCM positive electrode particle coated with Ga-LLZO, LATP and CNT, comprising: a positive electrode substrate, which is a carrier for carrying a positive electrode material; a positive electrode slurry layer coated on the positive electrode substrate, wherein the positive electrode slurry layer comprises: a positive electrode slurry containing a binder; a plurality of positive electrode particles are distributed in the positive electrode slurry, each positive electrode particle comprises: a NCM large particle; wherein the NCM large particle is in an irregular cubic shape, and its outer surface is covered with a plurality of Ga-LLZO fine particles (gallium-doped lithium lanthanum zirconium oxide compound) and a plurality of LATP fine particles (Li i 1+x A l x T i 2-x (PO 4 ) 3) to form a composite NCM large particle as a whole; wherein the Ga-LLZO fine particles are distributed in a convex arc shape on the NCM large particle, with a high middle and gentle ends; a Ga-LLZO interphase layer is formed between the bottom of the Ga-LLZO fine particles and the NCM large particle, and its main function is to guide lithium ions and secondly to protect the NCM large particle; wherein the LATP fine particles are distributed in a convex arc shape on the NCM large particle, with a high middle and gentle ends; a Ga-LLZO interphase layer is formed between the bottom of the LATP fine particles and the NCM large particle The LATP dielectric layer mainly serves as a protective layer and secondly as a guide for lithium ions. When lithium ions pass through the positive electrode, the channels for lithium ions can be dispersed through the guidance of the dispersed Ga-LLZO fine particles. The LATP fine particles can prevent the NCM large particles from being corroded by the electrolyte, and the LATP fine particles have higher lithium ion accommodation and current equalization capabilities for lithium ions. The Ga-LLZO fine particles, the LATP fine particles and the NCM large particles are all crystalline structures. The periphery of the composite NCM large particles is coated with CNT (Carbon Nanotube), which is a short-chain CNT with a length between 0.5 microns and 1 micron.

[0009] Furthermore, the NCM large particle size is 3 to 5 microns; it has a single crystal structure.

[0010] Furthermore, the radial thickness of the Ga-LLZO interphase layer is between 2 and 10 nanometers; the Ga-LLZO interphase layer is formed of Ga-LLZO and cobalt oxide.

[0011] Furthermore, the radial thickness of the LATP interphase layer is between 2 and 10 nanometers; the LATP interphase layer is formed by LATP and cobalt oxide.

[0012] Furthermore, the lateral size of the Ga-LLZO fine particles is between 100 and 280 nanometers; the lateral size of the LATP fine particles is between 50 and 100 nanometers.

[0013] Furthermore, the total weight of the Ga-LLZO fine particles relative to the weight of a single NCM large particle is between 0.5 and 0.8 wt %; the total weight of the LATP fine particles relative to the weight of a single NCM large particle is between 0.1 and 0.3 wt %.

[0014] Furthermore, the total weight of the CNT accounts for less than 0.25% of the weight of a single NCM large particle.

[0015] Furthermore, the short-chain CNT is used to bridge the Ga-LLZO fine particles and the NCM large particles, and to bridge the LATP fine particles and the NCM large particles.

[0016] The beneficial effects of the utility model are:

[0017] The utility model partially replaces part of the Ga-LLZO fine particles with the LATP fine particles, thereby reducing the negative reaction at the interface of the NCM large particles and reducing the cost of coating the NCM large particles. The ion conductivity of the LATP fine particles is lower than that of the Ga-LLZO fine particles. Using part of the Ga-LLZO fine particles to replace the LATP fine particles can reduce the overall production cost without changing the ion conductivity. In the utility model, the multiple Ga-LLZO fine particles are attached to the outer surface of the NCM large particles, because the ion conduction ability of the Ga-LLZO fine particles for lithium ions is much higher than that of the NCM large particles, and it will not produce negative reactions with lithium ions. Therefore, when lithium ions pass through the positive electrode, the channels of lithium ions can be dispersed through the guidance of the dispersed Ga-LLZO fine particles. Therefore, the design of the utility model can make lithium ions have better channels and greatly increase the performance of the overall battery. The LATP fine particles can prevent the NCM large particles from being corroded by the electrolyte, and the LATP fine particles have a higher lithium ion accommodation and current balancing capacity for lithium ions. The Ga-LLZO fine particles, the LATP fine particles and the NCM large particles in the utility model are all crystalline structures, so they have good overall stability and will not be easily released or dissociated, so the voltage of the entire battery can be increased.

[0018] The features and advantages of the present invention can be further understood from the following description, and please refer to the accompanying drawings when reading. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A structural diagram showing the positive electrode particles of the utility model;

[0020] Figure 2 A structural diagram showing the positive electrode of the utility model;

[0021] Figure 3 The structure diagram of the composite NCM large particles of the utility model is shown;

[0022] Figure 4 Another structural diagram showing the composite NCM large particles of the present invention.

[0023] Description of reference numerals:

[0024] 100, positive electrode;

[0025] 10. Positive electrode substrate;

[0026] 12. Positive electrode slurry layer;

[0027] 14. Cathode slurry;

[0028] 200, positive electrode particles;

[0029] 20. Composite NCM large particles;

[0030] 22. NCM large particles;

[0031] 24. Ga-LLZO fine particles;

[0032] 25. Ga-LLZO interphase layer;

[0033] 26. LATP fine particles;

[0034] 27. LATP interphase layer;

[0035] 30. CNT;

[0036] 32. Short-chain CNT. DETAILED DESCRIPTION

[0037] The structural composition of the present invention, as well as the effects and advantages it can produce, are now described in detail with reference to the drawings and a preferred embodiment of the present invention.

[0038] Please refer to Figures 1 to 4 As shown, the NCM positive electrode particles coated with Ga-LLZO, LATP and CNT of the utility model include the following elements:

[0039] like Figure 2 As shown, a positive electrode 100 of a general solid-state or quasi-solid-state battery includes:

[0040] A positive electrode substrate 10 is a carrier for supporting the material of the positive electrode 100;

[0041] A positive electrode slurry layer 12 is coated on the positive electrode substrate 10, wherein the positive electrode slurry layer 12 includes:

[0042] A positive electrode slurry 14 containing a binder, a plurality of positive electrode particles 200 are distributed in the positive electrode slurry 14, each positive electrode particle 200 includes: a large NCM particle 22, the size of the large NCM particle 22 is 3 to 5 microns; it is a single crystal structure. The proportion of the positive electrode particle 200 to the total positive electrode slurry 14 is 65 to 70wt%.

[0043] like Figure 1 As shown, the NCM large particle 22 is in an irregular cubic shape, and its outer surface is covered with a plurality of Ga-LLZO fine particles 24 (such as Li6.2Ga 0.8La3Zr2O12, gallium-doped lithium lanthanum zirconium oxide) and a plurality of LATP fine particles 26 (Li i 1+x A l x T i2-x (PO 4 ) 3 ) to form a composite NCM large particle 20. The lateral dimension of the Ga-LLZO fine particle 24 (i.e., the dimension along the spherical surface of the Ga-LLZO fine particle 24) is between 100 and 280 nanometers; the lateral dimension of the LATP fine particle 26 (i.e., the dimension along the spherical surface of the LATP fine particle 26) is between 50 and 100 nanometers. Basically, after sintering, the longitudinal dimension of the Ga-LLZO fine particle 24 and the LATP fine particle 26 along the radial direction of the sphere becomes shorter, the lateral dimension becomes wider, and the total volume remains unchanged. The total weight of the Ga-LLZO fine particle 24 is between 0.5 and 0.8 wt% relative to the weight of a single NCM large particle 22; the total weight of the LATP fine particle 26 is between 0.1 and 0.3 wt% relative to the weight of a single NCM large particle 22.

[0044] like Figure 3 As shown, the Ga-LLZO fine particles 24 are distributed in a convex arc shape on the NCM large particles 22, which is high in the middle and flat at both ends. A Ga-LLZO interphase layer 25 is formed between the bottom of the Ga-LLZO fine particles 24 and the NCM large particles 22, and its main function is to guide lithium ions, and secondly to protect the NCM large particles 22. The Ga-LLZO interphase layer 25 is mainly formed by the oxides of Ga-LLZO and cobalt (wherein the cobalt is mainly from the outer layer of the NCM large particles 22). Its function is to provide a better guiding channel for lithium ions. The Ga-LLZO interphase layer 25 is the interface oxygen-deficient layer and the extension layer generated by the Ga-LLZO fine particles 24 and the NCM large particles 22 during the sintering process. The Ga-LLZO interphase layer 25 helps connect the NCM macroparticles 22 and the Ga-LLZO fine particles 24, making them a continuous interface. The extended layer itself also has the ability of lithium ion conductivity, but it is slightly inferior to the Ga-LLZO fine particles 24. The radial thickness of the Ga-LLZO interphase layer 25 is between 2 and 10 nanometers.

[0045] like Figure 4As shown, the LATP fine particles 26 are distributed in a convex arc shape on the NCM large particles 22, which is high in the middle and flat at both ends. A LATP interphase layer 27 is formed between the bottom of the LATP fine particles 26 and the NCM large particles 22, which mainly serves as a protective layer and secondly guides lithium ions. The LATP interphase layer 27 is mainly formed by the oxides of LATP and cobalt (wherein the cobalt mainly comes from the outer layer of the NCM large particles 22). Its main function is to form a protective effect and prevent the NCM large particles 22 from being corroded by the electrolyte. The LATP interphase layer 27 is the interface oxygen-deficient layer and the extension layer generated by the LATP fine particles 26 and the NCM large particles 22 during the sintering process. This LATP interphase layer 27 helps the connection between the NCM large particles 22 and the LATP fine particles 26, making them a continuous interface, and the extension layer itself also has the ability of ion conduction, but it is slightly worse than the LATP fine particles 26. The radial thickness of the LATP dielectric layer 27 is between 2 and 10 nanometers.

[0046] The utility model partially replaces part of the Ga-LLZO fine particles 24 with the LATP fine particles 26, thereby reducing the negative reaction at the interface of the NCM large particles 22 and reducing the cost of coating the NCM large particles 22. The ion conductivity of the LATP fine particles 26 is lower than that of the Ga-LLZO fine particles 24. Using part of the Ga-LLZO fine particles 24 to replace the LATP fine particles 26 can reduce the overall production cost without changing the ion conductivity.

[0047] In the present invention, multiple Ga-LLZO fine particles 24 are attached to the outer surface of the NCM large particle 22, because the ion conduction ability of the Ga-LLZO fine particles 24 for lithium ions is much higher than that of the NCM large particle 22, and it will not produce negative reactions with lithium ions. Therefore, when lithium ions pass through the positive electrode 100, the channels of lithium ions can be dispersed through the guidance of the dispersed Ga-LLZO fine particles 24, so the design of the present invention can make lithium ions have better channels, and greatly increase the performance of the overall battery. The LATP fine particles 26 can prevent the NCM large particles 22 from being corroded by the electrolyte, and the LATP fine particles 26 have higher lithium ion accommodation and current balancing capabilities for lithium ions.

[0048] The Ga-LLZO fine particles 24, the LATP fine particles 26 and the NCM large particles 22 in the present invention are all crystalline structures, so they have good stability as a whole and will not be easily released or dissociated, so the voltage of the entire battery can be increased.

[0049] like Figure 1As shown, the periphery of the composite NCM large particle 20 is coated with CNT 30 (Carbon Nanotube), so the CNT 30 completely coats the composite NCM large particle 20 , and the whole forms the positive electrode particle 200 .

[0050] In the present invention, the CNT 30 is a short-chain CNT 32 , the length of which is between 0.5 micrometers and 1 micrometer. The overall weight of the CNT 30 accounts for less than 0.25% of the weight of a single NCM large particle 22 .

[0051] like Figure 1 As shown, the short-chain CNT 32 is used to bridge the Ga-LLZO fine particles 24 and the NCM large particles 22, and bridge the LATP fine particles 26 and the NCM large particles 22. CNT 30 is a very good conductive material.

[0052] CNT30 is used to increase the electronic conductivity, that is, to form a conductive bridge around the various Ga-LLZO fine particles 24 and the LATP fine particles 26, so that electrons can be conducted on the composite NCM large particles 20. Because CNT30 has extremely high conductivity, electrons can be conducted between different Ga-LLZO fine particles 24, LATP fine particles 26 and the NCM large particles 22 through CNT30, so the conductivity of the entire positive electrode is increased as a whole. The CNT30 can form different levels of cross-connections on the Ga-LLZO fine particles 24, the LATP fine particles 26 and the NCM large particles 22. The more CNT30 is added, the better the conductivity of the entire positive electrode 100.

[0053] The above structure can make the positive electrode 100 bear more lithium ions, so the whole positive electrode 100 can bear a higher voltage. For example, for a battery with an original voltage of 4.7V, the voltage can be increased from 4.7V to 4.9V by using the design of the utility model.

[0054] The advantage of using CNT30 in the present invention is that lithium ions can be easily stabilized between the CNT30, so the positive electrode slurry 14 in the present invention can stabilize a large number of lithium ions, thereby improving the overall conductivity of lithium ions, and electrons can be easily fixed between the short-chain CNT32, thereby improving the overall conductivity of lithium ions. Moreover, because the ion conductivity is very high, it helps the rapid charging and rapid discharging of the entire battery, and can also reduce the use of cobalt, thereby reducing the overall production cost.

[0055] The advantage of the utility model is that the outer surface of the NCM large particles is coated with many Ga-LLZO fine particles and LATP fine particles. Because the ability of the LATP fine particles to accommodate and evenly flow lithium ions is much higher than that of the NCM large particles, and the NCM large particles can be prevented from being corroded by the electrolyte, while extending the service life of the battery. In addition, multiple Ga-LLZO fine particles are attached to the surface of the multiple NCM large particles, and the Ga-LLZO fine particles also have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the channels of lithium ions can be dispersed through the guidance of the dispersed Ga-LLZO fine particles and the LATP fine particles, so the design of the positive electrode of the utility model can make lithium ions have better channels. The utility model also coats CNT30 on the outside of the NCM large particles coated with Ga-LLZO fine particles and LATP fine particles. The role of CNT30 is to form a conductive bridge around various different Ga-LLZO fine particles and LATP fine particles, so that electrons can be conducted on the composite NCM large particles. The framework of the utility model can provide stability for the overall positive electrode slurry structure, thereby reducing the amount of cobalt used.

[0056] The above detailed description is a specific description of a feasible embodiment of the utility model, but the embodiment is not intended to limit the patent scope of the utility model. Any equivalent implementation or modification that does not deviate from the technical spirit of the utility model should be included in the patent scope of the utility model.

Claims

1. A NCM positive electrode particle coated with Ga-LLZO, LATP and CNT, characterized in that: include: A positive electrode substrate is a carrier plate used to carry a positive electrode material; A positive electrode slurry layer is coated on the positive electrode substrate, wherein the positive electrode slurry layer comprises: A positive electrode slurry containing a binder; A plurality of positive electrode particles are distributed in the positive electrode slurry, each positive electrode particle comprising: a large NCM particle; The NCM large particle is in an irregular cubic shape, and its outer surface is covered by numerous Ga-LLZO fine particles and numerous LATP fine particles, forming a composite NCM large particle as a whole; The Ga-LLZO fine particles are distributed on the NCM large particles in a convex arc shape, which is high in the middle and flat at both ends; a Ga-LLZO interphase layer is formed between the bottom of the Ga-LLZO fine particles and the NCM large particles; The LATP fine particles are distributed on the NCM large particles in a convex arc shape, which is high in the middle and flat at both ends; a LATP interphase layer is formed between the bottom of the LATP fine particles and the NCM large particles; When lithium ions pass through the positive electrode, they can be guided by the dispersed Ga-LLZO fine particles to disperse the channels of lithium ions; the Ga-LLZO fine particles, the LATP fine particles and the NCM large particles are all crystalline structures; The periphery of the composite NCM large particle is coated with CNT, and the CNT is a short-chain CNT with a length ranging from 0.5 micrometer to 1 micrometer.

2. The NCM positive electrode particles coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The NCM large particle size is 3 to 5 microns; it is a single crystal structure.

3. The NCM positive electrode particles coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The radial thickness of the Ga-LLZO interphase layer is between 2 and 10 nanometers; the Ga-LLZO interphase layer is formed by Ga-LLZO and cobalt oxide.

4. The NCM positive electrode particles coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The radial thickness of the LATP interphase layer is between 2 and 10 nanometers; the LATP interphase layer is formed by LATP and cobalt oxide.

5. The NCM positive electrode particles coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The lateral size of the Ga-LLZO fine particles is between 100 and 280 nanometers; the lateral size of the LATP fine particles is between 50 and 100 nanometers.

6. The NCM positive electrode particle coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The total weight of the Ga-LLZO fine particles relative to the weight of a single NCM large particle is in the range of 0.5 to 0.8 wt %; the total weight of the LATP fine particles relative to the weight of a single NCM large particle is in the range of 0.1 to 0.3 wt %.

7. The NCM positive electrode particle coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The proportion of the total weight of the CNT to the weight of a single NCM large particle is less than 0.25%.

8. The NCM positive electrode particle coated with Ga-LLZO, LATP and CNT according to claim 1, characterized in that: The short-chain CNT is used to bridge the Ga-LLZO fine particles and the NCM large particles, and to bridge the LATP fine particles and the NCM large particles.